(untitled) (Research, Society and Development, 2020)
Objective: to review studies on education strategies for the prevention of Pneumonia Associated with Mechanical Ventilation (MVAP) implemented in health services and their effectiveness. Method: an integrative review carried out in September 2020, in five databases, using the following descriptors "education AND continuing and pneumonia AND ventilator-associated". The databases used in the search were: Scientific Electronic Library Online (SciELO), U.S. National Library of Medicine (PubMed). Through the Virtual Health Library (VHL), the following databases were accessed: Latin American and Caribbean Literature in Health Sciences (Lilacs), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (Medline). Results and discussion: 5 publications were included for the period between the years 2010 and 2020. Among the educational actions, workshops, bundle, lectures and intensive education courses were highlighted. The period of application of educational actions varied between 1 and 12 months. All studies showed improvements in results after the application of educational measures, but suggest continuing and permanent education and audits to maintain the effectiveness of the actions. Final Considerations: education strategies have proven to be effective in MVAP in the short term, however, they show the need for the application of permanent and continuing education in the hospital environment.